Implementation of the Natura 2000 Network in Poland – an Opportunity or a Threat to Sustainable Development of Rural Areas? Study on Local Stakeholders’ Perception - Chmielewski, Waldemar; Głogowska, Magdalena (Eastern European Countryside, 2024)
Conflicts related to the implementation of the Natura 2000 network can be found in Poland and other European countries. The general causes of those conflicts are known. Some of them lie in the habitat directive itself, and others are related to the transposition of the directive into national environmental law and management systems. The designation of Natura 2000 sites in Poland involved strong protests on a local level, mainly due to the lack of consultations with the stakeholders, or at least with the local governments. In those days, the common argument against the implementation of Natura 2000 was one of severe restrictions on the conduct of economic activities and infrastructure development. Eight years after the official implementation of Natura 2000 in Poland, we would like to state the research question as follows: “Is Natura 2000 a constraint on local development?” The paper presents the results of the research on the conflicts related to the Natura 2000 sites in Poland, and a perception of the Natura 2000 impact on the local economy, local community, and local citizens’ own situation, based on the questionnaire surveys conducted at the meetings, where management plans of the Natura 2000 sites were discussed. It appears that despite many cases of conflicts related to economical activities, new investments or infrastructure identified in municipalities with Natura 2000 sites in Poland, local stakeholders do not consider Natura 2000 only to be a restraint, but also an opportunity.